Reward and job satisfaction among the nurses in the Jaffna teaching hospital - Ajenthiny, J. (University of Jaffna, 2020)
Reward plays a major role in providing job satisfaction to the employees. The feeling of Job satisfaction can strengthen commitment and Loyalty and make the employees more productive and creative. In this study, the target population is the Nurses in Jaffna teaching hospital. The main objective of this study is to identify the relationship between the employee rewards and their job satisfaction and identifying the effect of both intrinsic and extrinsic reward on employee satisfaction. Through the questionnaire, using five-point Likert scales was used. Based on the analysis there is a positive relationship between extrinsic reward and intrinsic reward with job satisfaction and a positive relationship between payment, promotion, working condition, workgroup and recognition with Job satisfaction.
Keywords: extrinsic reward; job satisfaction; intrinsic reward